Carpal Tunnel Syndrome (CTS) at the Neurology Clinic of Dr. Soetomo General Academic Hospital - Ratih Dewi Anggraini Jubair Hegemur; Fidiana Fidiana; Meisy Andriana; Mudjiani Basuki (Universitas Airlangga, 2026)
Highlight: CTS is a frequent peripheral neuropathy that causes a variety of debilitating symptoms, underscoring the importance of understanding its clinical characteristics for better diagnosis and treatment. The study conducted at the Neurology Clinic of Dr. Soetomo General Academic Hospital, Surabaya, highlights consistent patterns in CTS patient characteristics. This provides valuable insights into CTS demographics and symptoms, which may contribute to the development of effective management strategies. ABSTRACT Introduction: Carpal Tunnel Syndrome (CTS) is a common neuropathy of the upper extremities, with a higher prevalence in women, particularly those aged 40 to 60 years. It is characterized by compression of the median nerve within the carpal tunnel, most frequently caused by hypertrophy of surrounding synovial tissue or inflammatory responses from extensive wrist use or trauma. Clinical symptoms include pain, tingling, numbness, and weakness, which often worsen at night. Diagnosis is typically based on clinical evaluation using the Phalen and Tinel tests, and is confirmed by electromyography (EMG) and nerve conduction studies (NCS). Recognizing CTS traits is essential for accurate diagnosis and appropriate management, which motivated this study. Objective: To describe the characteristics of patients with CTS treated at the Neurology Clinic of Dr. Soetomo General Academic Hospital, Surabaya. Methods: This is a descriptive cross-sectional study conducted using secondary data collected between January 2019 and December 2020. The study used electronic medical records (EMRs), comprising 44 CTS cases that met the predefined criteria. Data were processed using statistical software. Results: Among the 44 patients diagnosed with CTS, the majority were aged 45-64 years (63.7%), and were predominantly women (88.6%), with housewives comprising the largest occupational group (29.5%). Paresthesia was the most reported symptom (97.7%), and hypertension was the most common comorbidity (92.9%). All patients received non-operative therapy (100%). Conclusion: This study revealed that CTS predominantly affects early elderly individuals, particularly women and housewives, with paresthesia as the main symptom and hypertension as the common comorbidity. Non-operative treatment was the primary management strategy, yielding insights for future therapeutic strategies.